Health Status and Patient Satisfaction after Corneal Graft: Results from the Corneal Transplant Epidemiological Study - Adriano Fasolo; Cristina Capuzzo; Michela Fornea; Anna Chiara Frigo; Cristina Monterosso; Alfonso Zampini; Antonio Avarello; Alessandro Galan; Sandro Sbordone; Adele Elisabetta Ragucci; Claudio Gorla; Francesco Grigoletto; et al. (Journal of Ophthalmology)
Purpose. To evaluate effects of corneal transplantation on the health-related quality of life and patients’ satisfaction. Methods. Patients scheduled for elective penetrating or anterior lamellar keratoplasty completed by telephone interview the SF-12 Health Survey, before and one year after surgery, and a 6-item questionnaire on the satisfaction for graft outcomes. Results. The two questionnaires were answered by 1,223 patients. Transplantation did not influence the PCS-12 in males (ES=−0.01) and had a negative effect in females (ES=−0.18). Both sexes improved their MCS-12 (ES=0.18 and 0.23, resp.). The majority of patients (83.1%) were satisfied by the outcome of the graft. Conclusions. This is the first report on the use of the SF-12 and one of the few that assess quality of life in patients after corneal transplantation. We showed that grafting improves patients' health-related quality of life results of patients, influencing mental health (i.e., psychological attitude, social interaction, and emotions) with minor effects on physical health (limitation, pain, and vitality).